Vanadyl sulfate-enhanced oncolytic virus immunotherapy mediates the antitumor immune response by upregulating the secretion of pro-inflammatory cytokines and chemokines - Alluqmani, Nouf; Jirovec, Anna; Taha, Zaid; Varette, Oliver; Chen, Andrew; Serrano, Daniel; Maznyi, Glib; Khan, Sarwat; Forbes, Nicole E.; Arulanandam, Rozanne; Auer, Rebecca C.; Diallo, Jean-Simon (Frontiers in Immunology, 2022)
Oncolytic viruses (OVs) are promising anticancer treatments that specifically replicate in and kill cancer cells and have profound immunostimulatory effects. We previously reported the potential of vanadium-based compounds such as vanadyl sulfate (VS) as immunostimulatory enhancers of OV immunotherapy. These compounds, in conjunction with RNA-based OVs such as oncolytic vesicular stomatitis virus (VSVΔ51), improve viral spread and oncolysis, leading to long-term antitumor immunity and prolonged survival in resistant tumor models. This effect is associated with a virus-induced antiviral type I IFN response shifting towards a type II IFN response in the presence of vanadium. Here, we investigated the systemic impact of VS+VSVΔ51 combination therapy to understand the immunological mechanism of action leading to improved antitumor responses. VS+VSVΔ51 combination therapy significantly increased the levels of IFN-γ and IL-6, and improved tumor antigen-specific T-cell responses. Supported by immunological profiling and as a proof of concept for the design of more effective therapeutic regimens, we found that local delivery of IL-12 using VSVΔ51 in combination with VS further improved therapeutic outcomes in a syngeneic CT26WT colon cancer model.